Pengaruh Kepemilikan Institusional terhadap Kebijakan Dividen, dan Harga Saham - Lita Kurniawati; Sahala Manalu; Rony Joyo Negoro Octavianus (Universitas Kristen Maranatha, 2015)
This study aimed to get empirical evidence about the influence of institutional ownership on dividend policy and stock prices in the property and real estate companies. Data were analyzed using simple linear regression. These results indicate that (1) institutional ownership significant positive effect on dividendpolicy, where the higher ownership by institutions owned property and real estate company on the Stock Exchange, the higher dividends paid, (2) institutional ownership have a positive significant effect on stock prices, where the size of theshareholding by institutions on property and real estate company on the Stock Exchange will have an impact on stock price change.Keywords: Institutional Ownership, Dividend Policy, Stock Prices, and Property and Real Estate Company.